Medical Implant Production using Three-Dimensional Printing as a Potential Manufacturing Process in Medical Application / Siti Norsyahirah Abdul Razak ...[et al.] - Abdul Razak, Siti Norsyahirah; Abdullah, Jamaluddin; Md Akil, Hazizan (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
Three-dimensional printing (3DP) is one of the rapid prototyping (RP) technologies that can be a potential manufacturing process in medical application such as implant manufacturing. 3D printing is a layer manufacturing technique and can act as direct production of medical implant. In this research, implant manufacturing process by using MakerBot Replicator 2X 3D printer is proposed as improved alternative of the previous conventional implant production method. This study attempted to investigate the production time and production cost of medical implant manufacturing as compared to the conventional methods. As compared to the conventional method of implant manufacturing, the production time is much shorter than expected and the production cost is more affordable. The results show that 3D printer which is MakerBot Replicator 2X is feasible for direct production of implant manufacturing.